(untitled) (Archaeologia Adriatica, 2025)
This paper analyses pottery finds discovered during archaeological excavations in the historic core of Zadar in 2021, at a site located in the immediate vicinity of the city walls – Muraj. Alongside other finds, a significant quantity of pottery was uncovered, with this study focusing on coarse pottery and purified clay ware. The ceramics, as well as other artefacts, have been dated to the Late Middle Ages and Early Modern period.